The law of angels - Clark, Cassandra (New York : Minotaur Books, 2011)
York, 1385. Just as the Mystery Plays are about to unfold, a young woman witnesses a terrible crime and turns to Abbess Hildegard for protection.
Keywords: Hildegard, Abbess (Fictitious character) -- Fiction; Nuns -- Fiction; Artisans -- Fiction; Stained glass windows -- Fiction; Great Britain -- History -- Richard II, 1377-1399 -- Fiction; Yorkshire (England) -- Fiction; Mystery fiction; Historical fiction